Mengolah Hasil Personnel Assessment Test Dengan Metode Analytic Network Process (ANP) - Riyanto, Riyanto (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2011)
Nowadays, we watch and read on public media so many government officers were indicated to corrupt. The writer suggests that it is due to the failed methods of selection. There are many methods of competency assessment that can be used to select employees for a position, unfortunately the interdependencies between the selection criteria is less considered, so there is certainly a missing link between those criteria, they do not act as an integrated element. In this article, the writer proposes a method, in which some selection criteria are integrated, to obtain better results of competency assessment. This method is preceded by the determination of selection criteria, and then the interconnection between the criteria developed in a model of decision-making. The measurement of each criterion is done using a tool called the Analytic Network Process (ANP). The result is the value of the total weight of all criteria, and then it is ranked to get the top participants for selection.